Criminalidade econômica, empresa transnacional e o direito penal do inimigo - Gouveia, Wagner Camargo (2024)
This study deals with the accountability and consequent elimination from the economic market of companies created solely for the practice of criminal offenses, such as money laundering and organized crime. The analysis is carried out especially in relation to transnational companies, considering the difficulty in holding them responsible for harmful conduct and crimes. Economic Criminal Law, understood as a sub-branch of Criminal Law, seeking to protect and guarantee the economic order faces the challenge of penalizing “facade” or “ghost” companies, especially because Human Rights were fundamental in this fight, with the creation of conventions In this sense, however, the most relevant, a binding treaty on transnational companies, was not created, which is the desire of many. Faced with many legislative difficulties, both nationally and worldwide, such as the punishment of criminal legal entities, this thesis, supported by the theory of Günther Jakobs, or Criminal Law of the Enemy, which supports the separation or elimination of the enemy from the social sphere, proposes the extirpation of criminal enterprises, with the flexibility of some institutions, such as the punishment of preparatory acts and crimes of mere conduct, use of the Anti-Corruption Law, tightening of the Criminal Execution Law, among others. Therefore, the company created as a facade, only for illicit practices, which does not privilege the social function and the principles of the economic order, must be eliminated from the market. It is concluded that business lawfulness and care for the legal order cannot be seen as a choice, but rather an existential requirement. To this end, the hypothetical-deductive method was used with documentary and bibliographic analysis, in addition to the inductive method with the professional practice of the doctoral student.